2011
DOI: 10.1509/jppm.30.2.239
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Consequences of Risky Credit Behavior among College Students: Application and Extension of the Theory of Planned Behavior

Abstract: The Credit Card Act of 2009 reflects increased public policy concern about the risky credit behaviors of young adults. This act promotes increased responsibility of parents and implies that young adults must acquire financial knowledge and practice responsible financial behaviors. This study addresses this public issue by investigating the psychological processes underlying young adults’ risky credit card behaviors and the role of parents and financial knowledge in the financial behavior of young adults. A con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
261
3
25

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 269 publications
(311 citation statements)
references
References 26 publications
22
261
3
25
Order By: Relevance
“…Finally, the behavioural intention is seen as a key predictor of actual behaviour (Ajzen 1991(Ajzen , 2002Armitage and Conner 2001). The TPB has been validated in a wide range of domains (Ajzen 1991;Armitage and Conner 2001;Conner and Armitage 1998), including financial behaviours like budget keeping (Kidwell and Turrisi 2004), retirement saving (Croy, Gerrans, and Speelman 2010), saving habits (Loibl, Kraybill, and DeMay 2011), negative financial behaviours like not paying bills (Xiao et al 2011) and even future financial behaviours such as saving (Shim, Serido, and Tang 2012). However, it has not yet been applied to financial buffer saving.…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, the behavioural intention is seen as a key predictor of actual behaviour (Ajzen 1991(Ajzen , 2002Armitage and Conner 2001). The TPB has been validated in a wide range of domains (Ajzen 1991;Armitage and Conner 2001;Conner and Armitage 1998), including financial behaviours like budget keeping (Kidwell and Turrisi 2004), retirement saving (Croy, Gerrans, and Speelman 2010), saving habits (Loibl, Kraybill, and DeMay 2011), negative financial behaviours like not paying bills (Xiao et al 2011) and even future financial behaviours such as saving (Shim, Serido, and Tang 2012). However, it has not yet been applied to financial buffer saving.…”
Section: Theorymentioning
confidence: 99%
“…Furthermore, knowledge about behaviour has little to do with actually performing it (Ajzen et al 2011). Subjective knowledge, however, has a greater impact on behaviour (Lusardi, Keller, and Keller 2009;Wang 2009;Xiao et al 2011). Since several TPB-based studies found that subjective financial knowledge predicts financial attitude (Croy, Gerrans, and Speelman 2010;Kidwell and Turrisi 2004;Xiao et al 2011), our model assumes that individuals with more subjective financial knowledge have a greater tolerance of financial risks.…”
Section: Subjective Financial Knowledgementioning
confidence: 99%
See 2 more Smart Citations
“…According to Xiao et al (2011), the main source of financing consumption in the last few years has been usage of credit cards and accessible overdraft accounts to cover expenditures. Having not only one credit card makes students owing.…”
Section: College Student and Consumer Behaviormentioning
confidence: 99%